Poetry of the First World War : an anthology - Kendall, Tim.; Kendall, Tim, 1970- (New York : Oxford University Press, 2014)
A new anthology that combines generous selections from well-known soldier poets such as Wilfred Owen and Siegfried Sassoon with work by civilian and women poets. A general introduction places Great War poetry in its contexts and the work of each poet is prefaced with a biographical account that explains the circumstances of composition.
Thomas Hardy (1840-1928) -- A. E. Housman (1859-1936) -- May Sinclair (1863-1946) -- W. B. Yeats (1865-1939) -- Rudyard Kipling (1865-1936) -- Laurence Binyon (1869-1943) -- Charlotte Mew (1869-1928) -- Robert Service (1874-1958) -- Edward Thomas (1878-1917) -- Wilfrid Gibson (1878-1962) -- Mary Borden (1886-1968) -- Siegfried Sassoon (1886-1967) -- Rupert Brooke (1887-1915) -- Julian Grenfell (1888-1915) -- T. P. Cameron Wilson (1888-1918) -- Patrick Shaw Stewart (1888-1917) -- Ivor Gurney (1890-1937) -- Isaac Rosenberg (1890-1918) -- Arthur Graeme West (1891-1917) -- Wilfred Owen (1893-1918) -- Margaret Postgate Cole (1893-1980) -- May Wedderburn Cannan (1893-1973) -- Charles Sorley (1895-1915) -- Robert Graves (1895-1985) -- David Jones (1895-1974) -- Edmund Blunden (1896-1974) -- Edgell Rickword (1898-1982) -- Music-Hall and Trench Songs.
Includes bibliographical references (pages xxxi-xl) and index.
Keywords: English poetry -- 20th century; World War, 1914-1918 -- Poetry